Determining the Genetic Characteristics of Resistance and Virulence of the “Epidermidis Cluster Group” Through Pan-Genome Analysis - Sun, Zhewei; Zhou, Danying; Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Lu, Wei; Liu, Hongmao; Lu, Junwan; Lin, Xi; Li, Kewei; Xu, Teng; Bao, Qiyu; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Staphylococcus caprae, Staphylococcus capitis, and Staphylococcus epidermidis belong to the “Epidermidis Cluster Group” (ECG) and are generally opportunistic pathogens. In this work, whole genome sequencing, molecular cloning and pan-genome analysis were performed to investigate the genetic characteristics of the resistance, virulence and genome structures of 69 ECG strains, including a clinical isolate (S. caprae SY333) obtained in this work. Two resistance genes (blaZ and aadD2) encoded on the plasmids pSY333-41 and pSY333-45 of S. caprae SY333 were confirmed to be functional. The bla region in ECG exhibited three distinct structures, and these chromosome- and plasmid-encoded bla operons seemed to follow two different evolutionary paths. Pan-genome analysis revealed their pan-genomes tend to be “open.” For the virulence-related factors, the genes involved in primary attachment were observed almost exclusively in S. epidermidis, while the genes associated with intercellular aggregation were observed more frequently in S. caprae and S. capitis. The type VII secretion system was present in all strains of S. caprae and some of S. epidermidis but not in S. capitis. Moreover, the isd locus (iron regulated surface determinant) was first found to be encoded on the genomes of S. caprae and S. capitis. These findings suggested that the plasmid and chromosome encoded bla operons of ECG species underwent different evolution paths, as well as they differed in the abundance of virulence genes associated with adherence, invasion, secretion system and immune evasion. Identification of isd loci in S. caprae and S. capitis indicated their ability to acquire heme as nutrient iron during infection.